We Are Not Users Dialogues, Diversity, and Design - Subrahmanian, Eswaran (The MIT Press, 2020)
A call to reclaim and rethink the field of designing as a liberal art where diverse voices come together to shape the material world. We live in a material world of designed artifacts, both digital and analog. We think of ourselves as users; the platforms, devices, or objects provide a service that we can use. But is this really the case? We Are Not Users argues that people cannot be reduced to the entity called "user"; we are not homogenous but diverse. That buzz of dissonance that we hear reflects the difficulty of condensing our diversity into "one size fits all." This book proposes that a new understanding of design could resolve that dissonance, and issues a call to reclaim and rethink the field of designing as a liberal art where diverse voices come together to shape the material world. The authors envision designing as a dialogue, simultaneously about the individual and the social-an act enriched by diversity of both disciplines and perspectives. The book presents the building blocks of a language that can conceive designing in all its richness, with relevance for both theory and practice. It introduces a theoretical model, terminology, examples, and a framework for bringing together the social, cultural, and political aspects of designing. It will be essential reading for design theorists and for designers in areas ranging from architecture to software design and policymaking.